(untitled) (Al-Qamar, 2020)
Syed Kastīr Gul, commonly known as Kākā Ṣāḥib and Sheikh Raḥamkār, is a great mystic of 10th century. He is famous for his outstanding services for peace, love and harmony. Thousands of visitors and pilgrims come to his shrine every day for their spiritual satisfaction. This paper studies the opinions of Shaheed Benazir Bhutto University students about the role of Kākā Ṣāḥib and his shrine regarding the services of this great mystic for maintaining peace, harmony and love in the society. Results of the research are obtained by using qualitative and quantitative methods. The views of the students are displayed through tables and different shapes. Majority of the students have admitted that a mystic, through Islamic teachings, can play a significant role in creating peace and harmony in the society. Their thoughts demonstrate that Kākā Ṣāḥib spent his whole life for the service of humanity. Society can get huge inspiration from this pious personality and his shrine to avoid violence and to create a peaceful environment in the society.